Implementation of Islamic Education in Increasing the Religious Awareness of Senior High School Students - Mansur Mansur; Muh Ikhsan; Kamaruddin Kamaruddin; Samsuri Samsuri (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research examines the implementation of Islamic Education as a means to enhance the religious consciousness of high school pupils in Kendari. The research at hand addresses two key aspects: firstly, the religious consciousness among students attending State Senior High institution Kendari, and secondly, the implementation of Islamic teaching inside the institution. The data for this study were obtained through interview methods, participatory observation, and document analysis. The data analysis methodologies employed included data reduction, data display, and drawing conclusions. The present investigation revealed that the educational curriculum employed at the institution under scrutiny was the 2013 Islamic religious education curriculum. Based on the findings, it was determined that the level of religious awareness among students in this educational institution did not meet the anticipated standards. The 2013 curriculum serves as a metric for evaluating the religious views of students. This measure was implemented to ascertain if the religious beliefs held by the pupils were influenced by the teachings provided by their religion instructor within the educational institution. The correlation between the scope and diversity of Islamic religious education and the quantity and proficiency of Islamic religious education instructors inside this educational institution is not linear. The number of instructors responsible for delivering Islamic education within this educational institution is limited to a total of five individuals. A significant proportion of individuals has Master's degrees, indicating a high level of education attainment. Furthermore, the dissemination of significant Islamic religious education material is limited to a mere four sessions of 45 minutes each or three hours in total within a single week.